The triadic relationship between green HRM, innovation, and pro-environmental behaviour: a study of their interactions and impacts on employee productivity and organizational sustainability - Md. Abu Issa Gazi; Abdullah Al Masud; Md. Emon; Md. Ibrahim; Abdul Rahman bin S Senathirajah (Environmental Research Communications)
The study aims to examine the impact of Green Human Resource Management (GHRM) and eco-consciousness on work productivity, eventually resulting in greater efficiency and sustainability. Furthermore, we are also investigating the role of green innovation, environmentally conscious behavior, and employee productivity as mediators between green HRM and societal, economic, and environmental outcomes. Through the use of an online survey, 401 samples were collected from a variety of industries in Bangladesh, and then structural equation modeling was used to analyses the data. The study found that green HRM, innovation, and pro-environmental behavior favorably and significantly influence worker productivity. Furthermore, worker productivity directly and statistically affects social, economic, and environmental performance. The originality of this study resides in its comprehensive illustration of how GHRM, green innovation, and pro-environmental behavior effectively encourage worker productivity, resulting in organizational sustainability.